Electrochromism of Mesoporous Zinc Oxide/Carboxylated Viologen Electrodes. (18th June 2021) - Yamaguchi, H.; Saito, E.; Uno, K.; Yamakado, R.; Okada, S.; Yoshida, T.
Abstract : Combination of mesoporous metal oxide electrode with monolayer of adsorbed organic chromophore can be a promising strategy to achieve an energy-saving, non-emissive, non-volatile full-color electrochromic display (ECD) with a fast response. Here, we synthesized viologen molecules with one or two carboxylic acid groups as anchors, 1-(2-carboxyethyl)-1′-methyl-4, 4′-bipyridinium (CEMV) diiodide and N, N ′-bis(2-carboxyethyl)-4, 4′-bipyridinium (CE2 V) dichloride, adsorbed onto low temperature processed mesoporous ZnO electrodes to evaluate their electrochromic properties by in situ spectroelectrochemical measurements. CE2 V was adsorbed at 2.5 times higher concentration than CEMV. Fast and stable reversible electrochromism in two steps as white ⇄ purple ⇄ yellow and yellow ⇄ purple ⇄ yellow, with on/off response times as 3.3/0.5 s and 1.0/0.4 s, and retention of electrochromism for 85% and 70% of the initial values after 500 redox cycles were found for CE2 V and CEMV, respectively.